Study regarding the analysis of the agricultural subsidies from Romania compared to the E.U. between 2007-2017 - Daniela Nicoleta Bădan; Petruța Antoneta Turek-Rahoveanu; Diana Maria Necula (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
Every year the European Union grants a financial support to the agricultural sector of over 47 billion Euro, thus contributing to the completion of specific goals of the Common Agricultural Policy. The distribution of that EU funding towards the farmers from the member states is done according to the economical dimension of the exploitations, not according to the production level. In this study we intended to analyze the subsidies given to Romania after the admission to the EU compared to other member states. For a detailed analysis of the subsidies, quantitative as well as qualitative, we have taken account of the agricultural exploitations classification according to the economical dimension.
Keywords: Q14; Q18; 330; subsidies; economical dimension; PAC policies